2020
DOI: 10.1002/cche.10358
|View full text |Cite
|
Sign up to set email alerts
|

Relating amylose and protein contents to eating quality in 105 varieties of Japonica rice

Abstract: Background and objectives In rice, amylose and protein are the main factors that influence eating quality. The aim of this study was to determine the influence of the ranges in amylose and protein variation on rice eating quality and to explore the characteristics of amylose and protein in high eating‐quality rice varieties. A total of 105 japonica rice varieties (lines) from the middle and lower reaches of Yangtze River were studied. Findings When amylose content (AC) ranged from 7.35% to 19.98% and protein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 36 publications
1
27
1
Order By: Relevance
“…The contents of albumin and globulin are relatively low and mainly distributed in the aleurone layer, pericarp, and embryo (Shewry and Halford, 2002 ). Storage protein plays an important role in the rice quality and is closely related to the formation of chalkiness (Liu et al, 2020 ). This study showed that the storage protein accumulated rapidly at 15–20 DAA ( Figure 3 ), which was consistent with the study by Ashida et al ( 2013 ), indicating that the storage protein is mainly accumulated in the middle grain-filling stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contents of albumin and globulin are relatively low and mainly distributed in the aleurone layer, pericarp, and embryo (Shewry and Halford, 2002 ). Storage protein plays an important role in the rice quality and is closely related to the formation of chalkiness (Liu et al, 2020 ). This study showed that the storage protein accumulated rapidly at 15–20 DAA ( Figure 3 ), which was consistent with the study by Ashida et al ( 2013 ), indicating that the storage protein is mainly accumulated in the middle grain-filling stage.…”
Section: Discussionmentioning
confidence: 99%
“…Being the second largest storage components in rice grain, rice seed storage protein (SSP) accounts for about 8–10% of grain weight (Kawakatsu and Takaiwa, 2010 ). The grain protein content has been proved to be significantly negatively correlated with appearance, and increased temperature could regulate the grain protein synthesis, resulting in the changes in balance of storage substance, which could further regulate the formation of grain chalkiness (Tang et al, 2018 ; Liu et al, 2020 ). Studies also showed that reasonable nitrogen application could alleviate chalkiness caused by elevated temperature (Wada et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The sufficient supply of rice has led to dietary changes such as replacing coarse cereals (i.e., cereal grains other than rice and wheat) and whole grains (e.g., brown rice—the rice from which only the husk has been removed) with polished rice (i.e., white rice—the rice from which the husk, bran, and germ have been removed) 3 , 4 . More recently, as living standards improve in China, the production and consumption of good tasting rice, mainly soft-textured white rice with low amylose content, has substantially increased 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Rice with high amylose content (25–30%) tends to cook more firmly and with less stickiness, while rice with lower amylose content (<20%) tends to cook more softly and with greater stickiness [ 5 ]. The amounts of specific components such as protein and lipid also influence the cooking properties of rice [ 6 , 7 ]. More specifically, the protein content of rice was found to affect textural characteristics of cooked rice through competing with starch for water with the formation of disulfide bonds, while lipid restrains the moisture uptake of rice during cooking through the production of amylose–lipid complexes that impede leaching of amylose and swelling of starch [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the protein content of rice was found to affect textural characteristics of cooked rice through competing with starch for water with the formation of disulfide bonds, while lipid restrains the moisture uptake of rice during cooking through the production of amylose–lipid complexes that impede leaching of amylose and swelling of starch [ 6 ]. It was demonstrated that such differences in physicochemical properties directly influence the cooking and sensory qualities of rice [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%